Polyphenols and health - Croft, Kevin D. (2020)
Research in the field of polyphenols and their impact on health and disease has evolved considerably over the past decades.1 Not only has there been an exponential growth in the number of papers published, but also our understanding of these compounds has evolved from seeing them as simple antioxidants to recognising diverse bioactivity. In accordance, related disciplines, such as food chemistry, nutrition and medicine, started considering polyphenols as potential health promoters andinclusive, therapeutic agents.